The teaching of Character Education in grade six in Tarlac, Tarlac - Tabasondra, Iluminada S. 1925- ([Quezon City s.n.], 1963)
Teaching of Character Education or Good Manners and Right Conduct in public elementary schools in Tarlac, Tarlac was undertaken in this study. It was directed onto the qualifications of grade six teachers of Character Education, the methods of teaching and activities used, the selection of subject matter, the content of lessons taught, materials, devices, and visual aids utilized, and the measurement and evaluation of the outcomes of teaching.
Thesis (M.Ed.)--University of the Philippines
Keywords: Moral education -- Study and teaching